Optimized Extraction Conditions of Polysaccharides from Different Plants - Zhang, Heng; Tian, Minglei; Ho Row, Kyung (Asian Journal of Chemistry, 2013)
The optimal conditions for the extraction of polysaccharides from the Laminaria Japonica using in the hot-water method including alkalinity acidity, extracting time, temperature and sample to water ratio were examined. The contents of polysaccharides in Laminaria japonica, Salicomia herbacea, Hizikia fusiformis and Gelidium amansii were also compared. The optimal conditions were as follows: 90 ºC, neutral solution, dried sample to water ratio of 1/40 and heating time of 3 h. Under these conditions, the maximum amount of polysaccharides extracted from Laminaria japonica was 18.41 g/100 g dried sample. Among the four plants, Hizikia fusiformis had the highest polysaccharide content of 21.75 g/100 g dried sample, whereas Salicomia herbacea had the lowest.